Conflicts of interest among authors of the ESC guidelines for the management of atrial fibrillation. (25th November 2020) - Schneider, B; Stoellberger, C
Abstract: Background: In 2011, the Institute of Medicine (IOM) published standards for developing trustworthy clinical practice guidelines. It is recommended that "Whenever possible guideline development group members should not have conflicts of interest (COIs). In some circumstances, a guideline development group may not be able to perform its work without members who have COIs, such as relevant clinical specialists. Members with COIs should represent not more than a minority of the guideline development group members. The chair or cochairs should not be a person with COIs." Aim: Aim of the present study was to assess if the ESC guidelines for the management of atrial fibrillation are in accordance with the standards proposed by the IOM. Methods: The declaration of COIs from task force members (TFM) and reviewers of the 2010 and 2016 ESC atrial fibrillation guidelines were retrieved from the ESC homepage. The number and the type of COIs were assessed for each guideline and compared. Results: Regarding the 2010 guidelines, 8 of the 25 TFM (32%) reported no COI. In the remaining 17 TFM, 148 COIs were reported (8.7±10.2 per member, range 1–44). The chairperson declared 11 COIs. Consulting and advising was reported by 15 and research contacts by 13 TFM. Among the guideline reviewers, 12/26 (46%) reported no COI, and 14 reviewers declared 72 COIs (5.1±3.3 per reviewer, range 2–14). Regarding the 2016 guidelines, 3 of the 17 TFM (18%) reported no COI. The remaining 14 TFM declared 182 COIs (13.0±10.4 per member, range 1–32). The chairperson of the task force had the second most COIs (n=30). Direct personal payment was reported by 14 and research funding of the department by 10 TFM. Among the guideline reviewers, 16/79 (20%) reported no COI, and 63 reviewers declared 473 COIs (7.5±6.8 per reviewer, range 1–34). Comparing the 2010 and the 2016 guidelines, there was an increase of TFM with COIs (from 68% to 82%), of the number of COIs per TFM (from 8.7±10.2 to 13.0±10.4) and the COIs of the chairperson (from 11 to 30). Moreover, the proportion of TFM receiving personal payment (60% vs 82%) and the number of COIs due to personal payment (5.9±7.3 vs 7.7±7.4) were higher in the 2016 guidelines. In addition, more guideline reviewers had COIs in 2016 (54% vs 80%). Conclusion: The high and increasing rate of TFM and reviewers with COIs is not in accordance with the recommendations of the IOM. Since COIs can influence healthcare decision makers and may consciously or unconsciously influence choices made throughout the guideline development process, the ESC should follow the standards of the IOM. Funding Acknowledgement: Type of funding source: None